ALG3-CDG: a patient with novel variants and review of the genetic and ophthalmic findings - Farolfi, Martina; Cechova, Anna; Ondruskova, Nina; Zidkova, Jana; Kousal, Bohdan; Hansikova, Hana; Honzik, Tomas; Liskova, Petra (BMC ophthalmology, 2021)
BACKGROUND: ALG3-CDG is a rare autosomal recessive disease. It is characterized by deficiency of alpha-1,3-mannosyltransferase caused by pathogenic variants in the ALG3 gene. Patients manifest with severe neurologic, cardiac, musculoskeletal and ophthalmic phenotype in combination with dysmorphic features, and almost half of them die before or during the neonatal period. CASE PRESENTATION: A 23 months-old girl presented with severe developmental delay, epilepsy, cortical atrophy, cerebellar vermis hypoplasia and ocular impairment. Facial dysmorphism, clubfeet and multiple joint contractures were observed already at birth. Transferrin isoelectric focusing revealed a type 1 pattern. Funduscopy showed hypopigmentation and optic disc pallor. Profound retinal ganglion cell loss and inner retinal layer thinning was documented on spectral-domain optical coherence tomography imaging. The presence of optic nerve hypoplasia was also supported by magnetic resonance imaging. A gene panel based next-generation sequencing and subsequent Sanger sequencing identified compound heterozygosity for two novel variants c.116del p.(Pro39Argfs*40) and c.1060 C > T p.(Arg354Cys) in ALG3. CONCLUSIONS: Our study expands the spectrum of pathogenic variants identified in ALG3. Thirty-three variants in 43 subjects with ALG3-CDG have been reported. Literature review shows that visual impairment in ALG3-CDG is most commonly linked to optic nerve hypoplasia.
Keywords: Female; Congenital disorder of glycosylation; Arthrogryposis; vysoce účinné nukleotidové sekvenování; Optic nerve hypoplasia; novorozenec; Retinal Degeneration; Novel mutation; Mannosyltransferases; oči; ALG3-CDG; N-linked glycosylation; Infant; kojenec; Humans; Child, Preschool; Phenotype; High-Throughput Nucleotide Sequencing; Transferrin isoelectric focusing; degenerace retiny; lidé; fenotyp; Congenital Disorders of Glycosylation; vrozené poruchy glykosylace; Eye; ženské pohlaví; mannosyltransferasy; předškolní dítě; Infant, Newborn